Comparative Evaluation of Gingival Displacement by Using Retraction Paste and Retraction Cord- In-Vivo Pilot Study: Life Sciences-Periodontitis for Dental health - Dr Karunakar Shetty; Dr. Alghaydaa Saeed Alzhrani; Dr. Maha Khalil Alotaibi; Dr. Sarah Muteb Alotaibi; Dr. Razan Yousef Almaghrabi (International Journal of Life Science and Pharma Research, 2022)
Marginal integrity is one of the important principles of Tooth preparation. To achieve this, a satisfactory gingival displacement procedure is necessary. Aim of this study was to determine an appropriate gingival displacement and to access the gingival displacement on an unprepared tooth using retraction paste and impregnated retraction cord. Fourteen patients were chosen for this in vivo study. Oral prophylaxis was completed 15 days prior to the retraction procedure. Mandibular preliminary impressions were made using rubber base impression material. Gingival retraction procedure was carried out on the right and left 1st mandibular molars alternatively using retraction paste and retraction cord after 2 days of preliminary impression. Retraction paste was placed directly over the sulcus as per manufacturer’s instructions and kept for 2-3 minutes and rinsed and the required length of retraction cord was dispensed and placed into the gingival sulcus using a cord packer and cord was removed after 5 minutes. Post retraction measurements completed made an impression with rubber base impression material by using sectional tray alternatively. Statistical analysis was performed with ANOVA test, paired student t test with SPSS version 21. Patients were more comfortable with retraction paste as against gingival retraction cord with significance observed by observers 1, 3 and 4. (P<0.05). Retraction paste had significantly better retraction ability compared to retraction cord as observed by observer 1, 3 and 4 (p<0.05) whereas no significant difference was observed by observer 2(p>0.05). Retraction paste was significantly less time consuming compared to retraction cord as reported by observer 1 and 4 (P<0.05) and no significant differences between the two systems was reported by observer 3and 4(P>0.05.Within the limitations of the study, both retraction techniques showed adequate gingival retraction for the prosthesis and clinically insignificant differences were seen in both gingival retraction system regarding the retraction achieve. Retraction paste found to be easy for the control of hemorrhage and easy for placement and recommended to use where there is uncontrolled bleeding and sub-gingival finish lines of the tooth preparation However, the amount of vertical gingival retraction observed with the paste retraction system was significantly less than the medicated retraction cord.